CTIM-35. A PHASE II STUDY OF GITR AGONIST INCAGN01876 AND PD-1 INHIBITOR RETIFANLIMAB IN COMBINATION WITH STEREOTACTIC RADIOTHERAPY IN PATIENTS WITH RECURRENT GLIOBLASTOMA. (14th November 2022) - Bagley, Stephen; Shabason, Jacob; Mathew, Divij; Kothari, Shawn; Oldridge, Derek; Desai, Arati; Lustig, Robert; Kurtz, Goldie; Alonso-Basanta, Michelle; Chen, Kan; Long, Qi; Harsch, Jessica; et al.
Abstract: BACKGROUND: We evaluated the combination of retifanlimab, INCAGN01876, and FSRT in patients with recurrent GBM. METHODS: Phase II, single-center, 2 cohort study (A: single-arm non-surgical cohort; B, two-arm neoadjuvant/surgical cohort). Cohort A patients received pre-FSRT one-time doses of retifanlimab (500mg) and INCAGN01876 (300mg), FSRT (8 Gy x 3 fractions), and post-FSRT 28-day treatment cycles (retifanlimab, day 1; INCAGN01876, days 1, 15). Cohort B patients received pre-surgery doses of retifanlimab + INCAGN01876; subsequently, patients either went directly to resection (Sub-Arm 1) or to FSRT followed by resection (Sub-Arm 2). All patients resumed immunotherapy post-operatively. Primary endpoint: ORR in Cohort A. Data cut-off for this analysis was June 30, 2022. RESULTS: Thirty-two evaluable patients: Cohort A, n=16; Cohort B, n=16 (Sub-Arm 1, n=8, Sub-Arm 2, n=8). Median follow-up time: Cohort A, 13.6 months; Cohort B, 8.8 months. Forty-four percent women, median age 64 (IQR, 55–65), 56% MGMT unmethylated. Most common grade 3/4 treatment-related AEs included cerebral edema (25%), lymphopenia (16%), and cognitive disturbance (13%). Efficacy in Cohort A: no objective responses observed, best response of stable disease achieved in 9/16 patients (56%), median PFS 3.9 months (95% CI 2.1 – 6.2 months), median OS 9.8 months (95% CI 8.3 months – not reached [NR]). Efficacy in Cohort B: median PFS NR, median OS 15.1 months (95% CI 8.5 months – NR). Median PFS and OS are longer in Cohort B Sub-Arm 2 compared to Cohort B Sub-Arm 1 (PFS, NR vs. 2.2 months, p = 0.009; OS, NR vs. 8.5 months, p=0.026). Results of tissue and blood-based immune correlative analyses will be presented. CONCLUSIONS: The combination of retifanlimab, INCAGN01876, and FSRT is generally well-tolerated in patients with recurrent GBM when administered with or without surgical resection. Survival outcomes in the neoadjuvant cohort are encouraging, largely driven by patients that received neoadjuvant FSRT.